2020
DOI: 10.1016/j.ygeno.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights of Klebsiella pneumoniae isolated from a native Amazonian fish reveal wide resistome against heavy metals, disinfectants, and clinically relevant antibiotics

Abstract: A multidrug-resistant CTX-M-15-producing Klebsiella pneumoniae (KpP1 strain) was isolated from a native Amazonian fish ( Brachyplatystoma filamentosum ) at the Brazilian Amazon. The strain was identified by MALDI-TOF. The genome was extracted, purified and a Nextera DNA Flex library was prepared and sequenced by Illumina platform. The sequenced genome was de novo assembled using Unicycler and in silico prediction accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The CTX-M enzymes can be mostly clustered into five groups based on sequence homologies: CTX-M-1 (including CTX-M-15 and CTX-M-55), CTX-M-2, CTX-M-8, CTX-M-9 and CTX-M-25 [ 91 ]. ESBLs of seafood-origin reported to date comprise CTX-M-1, CTX-M-8, CTX-M-9, CTX-M-14, CTX-M-15, CTX-M-24, CTX-M-27, CTX-M-55, CTX-M-65, CTX-M-130, SHV-5, SHV-12, SHV-32, SHV-186, SHV-187, TEM-24, TME-52 and OXA in E. coli , Salmonella or other Enterobacterales [ 38 , 39 , 42 , 44 , 45 , 46 , 64 , 76 , 89 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. Additionally, class A PER-1 was identified from Vibrio parahaemolyticus of fish.…”
Section: Results (Headings As Per the Codex Guidelines)mentioning
confidence: 99%
“…The CTX-M enzymes can be mostly clustered into five groups based on sequence homologies: CTX-M-1 (including CTX-M-15 and CTX-M-55), CTX-M-2, CTX-M-8, CTX-M-9 and CTX-M-25 [ 91 ]. ESBLs of seafood-origin reported to date comprise CTX-M-1, CTX-M-8, CTX-M-9, CTX-M-14, CTX-M-15, CTX-M-24, CTX-M-27, CTX-M-55, CTX-M-65, CTX-M-130, SHV-5, SHV-12, SHV-32, SHV-186, SHV-187, TEM-24, TME-52 and OXA in E. coli , Salmonella or other Enterobacterales [ 38 , 39 , 42 , 44 , 45 , 46 , 64 , 76 , 89 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. Additionally, class A PER-1 was identified from Vibrio parahaemolyticus of fish.…”
Section: Results (Headings As Per the Codex Guidelines)mentioning
confidence: 99%
“…However, the parrot was a companion animal [confirmed through written confirmation with the corresponding author ( 94 )] which implies a possible human-companion animal transmission. The qnrE1 gene was also identified in a MDR K. pneumoniae isolate from a native Amazonian fish in Brazil where it was harbored in a hybrid IncFIB/IncHI1B plasmid ( 95 ). qnrE1 originated from the chromosome of Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Obire and Guda (2002) [ 38 ] demonstrated the presence of species belonging to the genera Klebsiella , Citrobacter , Escherichia and Enterobacter in leachates from a landfill in Nigeria, which is consistent with the results found in this study. Although species belonging to these genera have been associated with fecal contamination [ 39 ], their presence in highly complex matrices such as leachates is [ 40 ] mainly associated with their ability to tolerate and bioremediate heavy-metal-contaminated environments [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%